2017
DOI: 10.1063/1.4985543
|View full text |Cite
|
Sign up to set email alerts
|

A new torsion pendulum for gravitational reference sensor technology development

Abstract: We report on the design and sensitivity of a new torsion pendulum for measuring the performance of ultra-precise inertial sensors and for the development of associated technologies for space-based gravitational wave observatories and geodesy missions. The apparatus comprises a 1 m-long, 50 μm-diameter tungsten fiber that supports an inertial member inside a vacuum system. The inertial member is an aluminum crossbar with four hollow cubic test masses at each end. This structure converts the rotation of the tors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Therefore, it is impossible to determine exactly which variable is the exogenous variable of the model. Using the advantages of the regression model, the VAR model is the basis of empirical research [7]. In the post, the econometric significance and calculation results of each step are listed in detail.…”
Section: Vector Autoregressive Model Algorithmmentioning
confidence: 99%
“…Therefore, it is impossible to determine exactly which variable is the exogenous variable of the model. Using the advantages of the regression model, the VAR model is the basis of empirical research [7]. In the post, the econometric significance and calculation results of each step are listed in detail.…”
Section: Vector Autoregressive Model Algorithmmentioning
confidence: 99%
“…The torsion pendulum facility developed at the University of Florida serves as a test bed for gravitational reference sensors and associated technology for LISA [33]. The torsion pendulum consists of a suspended cross-bar assembly with four hollow, gold-coated, aluminum cubic test masses with the same dimensions as the LISA TMs (Figure 8.…”
Section: Torsion Pendulum Measurements -mentioning
confidence: 99%
“…The performance of the pendulum facility can be characterized by assessing the residual torque noise due to surface forces on the TM. Overall performance is limited by a number of factors discussed in detail in [33] including the angular readout of the pendulum, surface forces acting on the test masses in the two GRS, environmental disturbances, and the thermal noise of the suspension fiber. The typical performance of the pendulum during the study reported here is approximately 3 × 10 −13 N m/ √ Hz at 2 mHz comparable to the performance of other similar instruments [34,35].…”
Section: Torsion Pendulum Measurements -mentioning
confidence: 99%
See 1 more Smart Citation
“…The best way to run the apparatus in these conditions is to close the feedback loop on the optical lever, without closing the control loop with the interferometer, and to recover the interferometer sensitivity by subtracting the optical lever noise with an off-line analysis. The actuation system is composed of electrostatic actuators as typically used in the control of torsion pendulums [42,43]. In our case, the actuators are four metallic plates located at the sides of the balance beam.…”
Section: The Balance Prototypementioning
confidence: 99%